Upaya Meningkatkan Hasil Belajar PJOK Siswa dengan Model Experiental Learning Di Kelas V SD N 71/III Sungai Tanduk Tahun Pelajaran 2015/2016 - Arpani S.Pd (JURNAL MANAJEMEN PENDIDIKAN, 2016)
Abstract This study aims to determine students' learning outcome PJOK using experiential learning models in class V SDN 71 / III Horn River district. Kayu Aro District. Kerinci. This research is a classroom action research with research subjects fifth grade students SDN71 / III Horn River numbered 27 people. The object of this study is the implementation and the results obtained from the application of experiential learning models used data collection techniques are observation and tests. Data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that the implementation of learning with experiential learning models can improve student learning outcomes SDN71 class V / III Horn River. Improved learning with experiential learning models in the first cycle of student activity increased 63.87% in the second cycle into 81.48%. The average value of student learning outcomes obtained in the first cycle of 65.56 increased to 72.96 in the second cycle. Students who achieve a value ? 65 on the first cycle as many as 18 people or 62.97%. In the second cycle increased to 23 people or 81.48%. Thus, learning the model of experiential learning on subjects PJOK can be used in class V SDN71 / III Horn River.Keywords: Learning Outcomes, PJOK, Experiental Learning Model